STATUS GIZI MIKRO BAYI DENGAN JENIS MAKANAN PENDAMPING ASI (MP-ASI) BERBEDA DI KABUPATEN BOGOR - Sukati Saladin; Muherdiyantiningsih Muherdiyantiningsih (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2008)
Micronutrient Status of Infants With Different Kind of Complementary Feeding In Bogor District.Background: Breast milk as the main resource of nutrient intake for infants is sufficient only within the first six months period of their life. However for the next period it is necessary to be completed their nutrient intake by supplementary feeding since the excretion of breast milk become decreased.Objectives: To find out the figure of micronutrients status (vitamin A and iron) based on serum retinol and hemoglobin (Hb) and nutrition status (weight for age and length for age) of infants consuming supplementary feeding made by mother at household level compare to those who received manufactured product.Methods: The design of the study is cross-sectional. The subjects of study were healthy infant, 2-10 months old, consuming breast milk and supplementary feeding.Results: There was no significant difference of the average of serum retinol of infants less than 6 months old received supplementary feeding made by mother (0.62 ± 0.2181 umol/L) and those of manufactured product (0.71 ± 0.2051 umol/L).There was no significant difference of Hb value of both groups (10.4 ± 0.790 g/dl compared 10.6 ± 1.191 g/dl). According to z-score point there was also no significant difference of nutrition status based on indexes of weight for age (+ 0.010 ± 0.983 compared + 0.067 ± 1.029) and length for age (-0.510 ± 1.291 compared - 0.409 ±1 .291) of infants received supplementary feeding made by mother compared to those of manufactured. The average of serum retinol of infants >6 months old received manufactured supplementary feeding was significantly higher (p < 0.05) than those of made by mother (0.81 ± 0.258 umol/L compared 0.64 ± 0.218 umol/L). There was no significant difference (p>0.05) of Hb value of infants received supplementary feeding made by mother and those of manufactured (10.5 ± 1.210 g/dl compared 10.7 ± 1.195 g/dl). Z-score point showed significant difference of nutrition status based on indexes of weight for age (0.323 ± 1.163 compared - 0.914 ± 0.896) and length for age (- 0.559 ± 1.184 compared 1.242 ± 0.844) of infants received manufactured supplementary feeding compare to those of made by mother.Conclusions: The effect of manufactured supplementary feeding was significantly better to improve micronutrient status especially serum retinol and nutrition status based on weight for age and length for age of infant >= 6 months old than those of made by mother.Keywords: micronutrient status, nutrition status, supplementary feeding.